Ultrasound-assisted fermentation enhances bioethanol productivity - Ahmad Ziad, Sulaiman; Azilah, Ajit; R. M., Yunus; Chisti, Yusuf (journal homepage: www.elsevier.com/locate/bej, 2011)
Production of ethanol from lactose by fermentation with the yeast Kluyveromyces marxianus (ATCC 46537)under various sonication regimens is reported. Batch fermentations were carried out at low-intensity sonication (11.8Wcm−2 sonication intensity at the sonotrode tip) using 10%, 20% and 40% duty cycles. (A duty cycle of 10%, for example,wasequivalent to sonication for 1 s followed by a rest period (no sonication)of 10 s.) Fermentations were carried out in a 7.5 L (3 L working volume) stirred bioreactor. The sonotrode was mounted in an external chamber and the fermentation broth was continuously recirculated between the bioreactor and the sonication chamber. The flow rate through the sonication loop was 0.2 L min−1.All duty cycles tested improved ethanol production relative to control (no sonication). A 20% duty cycle appeared to be optimal. With this cycle, a final ethanol concentration of 5.20±0.68 g L−1 was obtained, or nearly 3.5-fold that of the control fermentation. Sonication at 10% and 20% cycles appeared to stimulate yeast growth compared to the control fermentation, but 40% duty cycle had a measureable adverse impact on cell growth. Sonication at 10% and 20% cycles enhanced both the extracellular and the intracellular levels of -galactosidase enzyme. Although at the highest duty cycle sonication reduced cell growth, cell viability remained at ≥70% during most of the fermentation. Sonication at a controlled temperature can be used to substantially enhance productivity of bioethanol fermentations